Leopardi and the mysterious "ticket". Memory exercises or incomprehensible lines? (Prassi Ecdotiche della Modernità Letteraria, 2021)
The essay provides an original interpretation of the origin and the meaning of a curious paper in endecasyllables kept among the manuscripts of Giacomo Leopardi at the National Library of Naples, which modern publishers usually call Esercizi di memoria. Leopardi used to write preparatory verses, in particular for his Zibaldone, probably when he did not have the opportunity to devote himself to the drafting of the diary as in Recanati. This activity probably took place in the periods when Leopardi was in travel: the notes probably served to fix ideas and thoughts to be developed, and the verse form provided the author with an occupation during his travels in carriage. The hypothesis therefore proposed is that Leopardi could have written at least part of the recto of this paper during his travel in Rome in 1822-23, when the writing of the Zibaldone was practically interrupted, in order to fix ideas to be developed on his return. Finally, the essay aims to reconstruct the plots that connect books, facts and people in the "labyrinth of associations" built by Leopardi at the time of writing.
Keywords: Leopardi; Giacomo Leopardi; Zibaldone; unpublished works; autographs; Biblioteca Nazionale di Napoli